Influence of Advertising on the Adoption of Green Products: The Mediating Role of Innovativeness - Ahlafi, Hanane; Noura, Noura; Bahoussa, Abdelaziz; Hassainate, Mohammed (International Journal of Engineering and Technology, 2019)
Ecology as a strategic variable has been the focus of interest for researchers since the early seventies (Marguerat & Cestre 2002). As early as the pioneering researches of Hénion (1976), Kassar Jian (1971), Kinnear and Taylor (1973) and Kinnear et al (1974), the ecological dimension had been integrated into the research and practice of management and marketing. In addition, some authors agree that different stakeholders such as consumers, NGOs, public authorities, advertisers and publicists are increasingly informed and aware about the importance of protecting their environment (Schlegelmilch & Pollack 2005).However, some authors denounce the inaction of consumers although they are aware of the degradation of their environment. This passivity is explained among other things by the high price of green products compared to traditional products (Green Brands2011).In this study, we first presented the research problem, and then we analyzed the works related to the typologies of green consumers and the main variables that we consider to be determinants of the adoption of so-called green products. Finally, we exposed the research hypotheses, the conceptual model, highlighting the mediating role of innovativeness in the relationship between the attitude towards advertising and the adoption of green products.